An introduction to iOS programming from getting the SDK to submitting your first app - Allan, Alasdair (O'Reilly, 2012)
"Learn all of the steps necessary for building your first native iOS app. With this introductory video course, experienced iOS developer Alasdair Allan walks you through the entire process, from downloading the latest developer tools to submitting your finished app to Apple's App Store. This course is refreshed and updated for iOS 5 and Xcode 4"--Resource description page
Title from title screen
Keywords: iOS (Electronic resource); Application software -- Development; Mobile computing -- Programming; iPhone (Smartphone) -- Programming; iPad (Computer) -- Programming; Logiciels d'application; Développement; Informatique mobile; Programmation; iPhone (Téléphone intelligent); Programmation; iPad (Ordinateur); Programmation; Application software; Development